Measuring Tumor Microenvironment pH During Radiotherapy Using a Novel Cerenkov Emission Multispectral Optical Probe Based on Silicon Photomultipliers - Oraiqat, Ibrahim; Al-Snayyan, Essam; Calcaterra, Andrew; Clarke, Roy; Rehemtulla, Alnawaz; El Naqa, Issam (Frontiers in Physics, 2021)
Cerenkov Emission (CE) multispectral analysis with silicon photomultiplier (SiPM)-based optical probes are promising tools for online tumor microenvironment interrogation and targeting during radiotherapy delivery. With the extreme sensitivity of SiPMs, deep tissue multispectral CE measurements can be realized in a clinical setting. In this work, we utilize our Cerenkov Emission Multi-spectral Imaging (CMSI) prototype probe to interrogate spectral components of the CE generated during external beam radiotherapy. This enables us to probe in vitro quantitative changes in the pH of cell media to monitor cancer cell proliferation after various treatment pathways and demonstrate the probe’s ability to differentiate between varying treatment resistance cell lines. The feasibility of using the CMSI probe in vivo was also successfully demonstrated by measuring tumor pH during a pilot mouse study.